China's diplomacy in Eastern and Southern Africa - Adem, Seifudein (International political economy of new regionalisms series, 2013)
In contemporary discourse on China-Africa relations, there are three differing perspectives. On one hand Sino-pessimists view China as a giant, feeding on Africa's resources to fuel its own industrialization. On the other hand, Sino-optimists see China as a benevolent state capable of 'developing' the continent.